Thermal and electrical simulation of high voltage ceramic cap and pin disc type insulator assembly. (27th October 2014) - Palhade, R.D.; Tungikar, V.B.; Dhole, G.M.; Kherde, Sanjay M.
In this paper, an attempt is made to study accurately, the temperature, potential and electrical field distribution for the 11 kV single cap and pin ceramic disc type insulator assembly. The FE coupled field thermo-electrical computer simulation is carried out by using a commercially available software Ansys-11. The simulation results obtained are analysed and compared with individual FE thermal and FE electrical simulations. It is observed that the thermal and electrical loads are coupled like observed in other thermo-electrical machines/systems. However, this coupling effect of a thermal and electrical load was not those of prominent to either change the thermal or electrical characteristics of an insulator assembly. This indicates that the coupled field simulation can provide considerable accurate information of temperature, potential and field distribution in insulator assembly and its effects by considering the actual working field condition, i.e., thermal and electric loads acting simultaneously as compared to individual FE thermal and FE electrical simulations.